1980
DOI: 10.1007/bf00137452
|View full text |Cite
|
Sign up to set email alerts
|

New investigations concerning the relationships between congenital colour vision defects and road traffic security

Abstract: New extentive experiments demonstrated that: (a) protan observers are more deficient than deutan ones with regard to perception distances of some traffic panels, of vehicle red stop lights, of vehicle red rear-position lights and of white, yellow and red reflectors. Contrarily, deutan observers are more deficient than protan ones for the distinction of differently coloured traffic lights and vehicle rear lights; (b) protan and deutan drivers are nevertheless not responsible for more traffic accidents than driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 10 publications
(6 reference statements)
1
36
1
Order By: Relevance
“…This is because of the absence of their L cone photopigment in the case of protanopia or a shift of the spectral absorptance of the L cone photopigment to shorter wavelengths in the case of protanomaly. The loss of red light sensitivity is substantial: it can reduce the distance from which red signals can be seen by up to 40 per cent 28,29 and can slow response time to red signals. 30 The loss of red light sensitivity occurs in both protanopes and mildly affected protanomals.…”
Section: Medmont C-100 Test Cmentioning
confidence: 99%
“…This is because of the absence of their L cone photopigment in the case of protanopia or a shift of the spectral absorptance of the L cone photopigment to shorter wavelengths in the case of protanomaly. The loss of red light sensitivity is substantial: it can reduce the distance from which red signals can be seen by up to 40 per cent 28,29 and can slow response time to red signals. 30 The loss of red light sensitivity occurs in both protanopes and mildly affected protanomals.…”
Section: Medmont C-100 Test Cmentioning
confidence: 99%
“…There have been few investigations of this and they either have samples that are too small or have a design that cannot take account of confounding variables. Even so, there is evidence of an association that abnormal colour vision is a risk factor in driving in the data of Verriest and colleagues, 2 when it is re-analysed. 3 It is unlikely to be a dominant risk factor but it would be wise not to promote the notion that it is not a risk factor until a very well designed investigation fails to show an association.…”
mentioning
confidence: 99%
“…Some experimental studies of coloured signal recognition, often involving simulations, have indicated that people with defective colour vision make more errors recognizing the colours of road traffic signals than do those with normal colour vision (Nathan et al 1964;Verriest et al 1980aVerriest et al , 1980bFreedman et al 1985). Protans have difficulty seeing red signal lights because of their reduced sensitivity to long wavelength light and because red signals have lower intensities than green and yellow signals because of the lower transmittance of red filters (Cole & Brown 1966;Cole 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Protans have difficulty seeing red signal lights because of their reduced sensitivity to long wavelength light and because red signals have lower intensities than green and yellow signals because of the lower transmittance of red filters (Cole & Brown 1966;Cole 2002). However, drivers with defective colour vision can and do use the position of the illuminated signal to infer its colour (Verriest et al 1980a(Verriest et al , 1980b and they also use the movement of other traffic as prompts. The evidence that drivers with defective colour vision have more accidents is equivocal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation